2021
DOI: 10.1007/s10103-021-03289-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Na and K in anti-diabetic ayurvedic medicine using LIBS

Abstract: Diabetes mellitus, known as diabetes, is a challenging issue, and to control diabetes, a large population is lining toward ayurvedic medicine. In the present study, four brands of anti-diabetic ayurvedic medicines, along with a home remedy, are analyzed using the laser-induced breakdown spectroscopic (LIBS) technique. The study is carried out to know the elements responsible for glycemic potential. The laser-induced breakdown (LIB) spectra elucidate the presence of organic and inorganic elements like Al,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
(38 reference statements)
3
2
0
Order By: Relevance
“…Therefore, it is essential to evaluate the actual concentration and ratios of elements present in any medicine in order to correlate their specific bioactivity with specific elemental ratios. Kumari et al evaluated the ratio of minerals helpful in diabetic management and concluded that in most ayurvedic antidiabetic medicine the ratio of Mg/Na and Mg/K are approximately the same [24]. The present work also confirms, as shown in Figure 3, that the ratios of spectral intensity of Mg/Na and Mg/K are the same in t. dioica sample.…”
Section: Determination Of the Elemental Compositionsupporting
confidence: 84%
See 2 more Smart Citations
“…Therefore, it is essential to evaluate the actual concentration and ratios of elements present in any medicine in order to correlate their specific bioactivity with specific elemental ratios. Kumari et al evaluated the ratio of minerals helpful in diabetic management and concluded that in most ayurvedic antidiabetic medicine the ratio of Mg/Na and Mg/K are approximately the same [24]. The present work also confirms, as shown in Figure 3, that the ratios of spectral intensity of Mg/Na and Mg/K are the same in t. dioica sample.…”
Section: Determination Of the Elemental Compositionsupporting
confidence: 84%
“…The importance of various bio-elements in the medicinal activity of plants cannot be ignored and thus it becomes imperative to detect their presence, concentrations, and ratios in which they are present in T. dioica leaves sample. Hence, the anti-diabetic activity of T. dioica leaves could be correlated not only with the presence of Na, K, and Mg but also with the assessment of specific ratios of Mg/Na and Mg/K, which are just the same as in the earlier results of other anti-diabetic ayurvedic medicines [24]. For CF-LIBS one utilizes recorded intensities of different spectral lines of the elements, however, the laserinduced plasma needs to fulfill three cconditions that must be verified: (i) plasma must be stoichiometric, (ii) plasma must be optically thin, and (iii) plasma must show local thermal equilibrium [26][27][28].…”
Section: Quantitative Analysissupporting
confidence: 55%
See 1 more Smart Citation
“…This method features rapid detection, simple sample preparation, real-time online detection of multiple elements, and a small sample size requirement [15,16]. It has been employed extensively in food analysis [17], coal metallurgy [18], environmental monitoring [19], and medical diagnosis [20].…”
Section: Introductionmentioning
confidence: 99%
“…Hypoglycemia is a condition in which blood glucose levels are below normal limits, less than 70 mg/dl [11,12]. In the event of hypoglycemia, the body defence mechanism that functions to activate when several neuroendocrine systems are disrupted, causing the body's failure to maintain normal blood glucose levels, either by external or internal causes [13].…”
Section: Introductionmentioning
confidence: 99%